Brazil : Trade Policies to Improve Efficiency, Increase Growth, and Reduce Poverty - World Bank (Washington, DC, 2013)
This comprehensive report-actually four compartmentalized reports in one-- focuses on policies to improve Brazil's trade performance. Specifically, three questions are addressed: What are the merits of alternative trade liberalization or integration options ? What domestic policies should be adopted to enhance Brazil's export response to trade openness? What policy options in the area of international services trade negotiations can improve access to foreign markets and enhance the value of overall trade reforms? In Part 1, Chapter 1examines regional, multilateral, and unilateral trade policies. Chapter 2 overviews export performance, surveys the overall policy environment facing potential and actual exporters, and identifies the main areas where policies could be improved to help enhance export performance. Lastly, Chapter 3 discusses how regional and multilateral negotiations can be used to support domestic reform and improve access to foreign markets. Part 2 provides quantitative estimates to answer questions about the efficacy of unilateral liberalization and multilateral trade agreements. After an introductory chapter, Chapter 2 describes the model and data. Chapter 3 presents and explains the policy results for Brazil, the implications for the distribution of income, and the reallocation of output among sectors. Results for other countries in the model are also explained. The impact on partner and excluded countries of the regional arrangements are also evaluated and compared to the impact under multilateral trade liberalization. Chapter 4 examines how the various trade policy options may be combined to optimize the outcome for Brazil. The conclusions are in Chapter 5. In Part 3, Chapter 1 briefly discusses overall macroeconomic context and the arguments for fostering greater export growth. Chapter 2 provides an overview of export performance in recent years. This is followed in Chapter 3 by an examination of the government institutional environment for policy-making related to exports. Chapter 4--the main section in this part-discusses the policies affecting export behavior. An emphasis has been placed on the results of interviews conducted with exporting firms. The final section--Chapter 5--provides some suggestions and recommendations for policies. In Part 4, Chapter 1 provides a backdrop to this section. Chapter 2 describes the pattern of Brazil's trade in services, drawing upon balance of payments statistics and data on foreign direct investment inflows. Chapter 3 reviews Brazil's services trade and investment policy in services. Chapter 4 examines Brazil's export interests. Chapter 5 provides an economic analysis of the choice Brazil faces between regional and multilateral approaches to liberalization of trade in services. Chapter 6 offers a critical review of the rules of existing international agreements on trade in services that are most relevant to Brazil. Finally, Chapter 7 seeks to synthesize the insights emerging from Chapters 2-6.